Lesbian, gay, bisexual, and transgender parents seeking health care for their children: A systematic review of the literature - Shields, L.; Zappia, Tess; Blackwood, Diana; Watkins, R.; Wardrop, Joan; Chapman, R. (Blackwell/Wiley, 2012)
Background: Few studies have examined the issues faced by lesbian, gay, bisexual, and transgender (LGBT)-parented families in relation to their access to and satisfaction with healthcare services for their children. It is thought that LGBT individuals have experienced negative interactions with the healthcare environment. Aims: To systematically review the literature investigating the experience of LGBT parents seeking health care for their children. Methods: A search of the following databases: Cochrane Library, CINAHL, Embase, Google Scholar, Medline, PsychInfo, Science Direct, Sociological Abstracts, Proquest, Scopus, and Web of Science was conducted. Using the PRISMA flow chart and processes of the United Kingdom Centre for Reviews and Dissemination, we selected and analysed relevant studies. Findings: Four studies that met the inclusion criteria were identified. Studies showed that while the experience of LGBT parents seeking health care was largely positive, strategies need to be implemented to improve the quality of healthcare services for LGBT families and ensure that their needs are met. Discussion: Although many LGBT parents have positive experiences of health care, some still experience discrimination and prejudice. Implications for practice: Specific educational interventions are needed to support LGBT parents seeking health care for their children. Conclusions: Further research is required to explore LGBT-parented families’ experiences of healthcare services, and this should include children's experiences.